Dehumidifying material for solar cell packaging and preparation method and application thereof
By combining silica and specific dehumidification materials on glass fibers, adsorbing water vapor, the problem of water vapor penetration in solar cells in high temperature and high humidity environments is solved, and the components' high temperature and high humidity resistance and conversion efficiency stability are significantly improved. .
Patent Information
- Application Number
- CN202411295375.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-10
AI Technical Summary
Existing solar cells are prone to water vapor infiltration in high temperature and high humidity environments, resulting in corrosion and degradation of battery modules. The barrier effect of existing water-blocking materials is not good enough to effectively solve the impact of water vapor on the battery.
Dehumidification materials are used to install silica and specific types of dehumidification molecular sieves (13X, 5A, 4A, 3A molecular sieves) on glass fibers. By adsorbing water vapor, the influence of water vapor on solar cell modules is prevented, the packaging effect is improved, and the module resistance is improved. High temperature and high humidity performance.
Effectively adsorbing and permeating the water vapor into the solar cell module significantly suppresses the performance attenuation under high temperature and high humidity conditions and improves the conversion efficiency stability of the solar cell.
Smart Images

Figure CN119281293A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a dehumidification material for solar cell packaging and a preparation method and application thereof. Background Art
[0002] To reduce the cost of generating electricity from photovoltaic (PV) systems, the lifetime of PV modules (i.e., up to 20% relative performance degradation) should be at least 25 years or ideally 50 years, which makes long-term stability even more critical. Bifacial passivated emitter and rear cell (PERC), heterojunction (HJT), and tunnel oxide passivated contact (TOPCon) solar cells are mainstream silicon cell technologies that have high efficiency and manufacturability. Despite the technological advancement, some cell technologies (such as heterojunction and TOPCon) still face reliability issues, which can lead to large power losses under high humidity. This is especially true when they are encapsulated with low-cost materials (such as EVA). To prevent these problems, bifacial heterojunction and TOPCon cells are usually encapsulated with polyolefin elastomer (POE) or thermoplastic polyolefin (TPO), while glass plates are set on the front and back. In some cases, edge sealants are also used to obtain more stable modules. However, the use of sealants can only reduce the infiltration of water vapor and reduce the moisture content released by the encapsulation material itself, and cannot fundamentally solve the problem of cell degradation caused by water vapor.
[0003] Degradation during field and / or indoor humidity testing is metal contact corrosion, which increases the series resistance (Rs) of the cell over time, which can lead to performance loss. The root cause of this corrosion is believed to be the electrochemical reaction between moisture, various contaminants, and the metal contacts of the solar cell. Contaminants may include acetic acid from the hydrolysis of EVA. In addition, residual solder flux has been shown to play a key role in contact corrosion, mainly due to the presence of organic acids and / or halide materials, which chemically react with moisture and metal contacts, resulting in an increase in the series resistance Rs.
[0004] In hot and humid climate areas, high temperature and high humidity conditions have thermal aging and hydrolysis aging effects, which have a significant impact on the cells, backplanes, and sealing materials in the components. For example, double-glass components that have been used for 15 years in a certain place in Hainan almost all have problems with cell and solder strip corrosion. Some components have the phenomenon of cell and packaging material separation. In the junction box, due to water vapor passing through the holes in the back glass, the packaging material delaminates. These double-glass components use aluminum alloy frame edge sealing, but still cannot prevent water vapor from entering the components.
[0005] In the prior art, battery cells are usually connected in series or in parallel with welding strips and bus bars, and encapsulated in glass and backplanes. Aluminum frames are installed around to ensure the mechanical strength of the components. The number of batteries in series determines the size of the component voltage, and the area of a single battery determines the current of the component. The welded batteries will be stacked with the packaging materials. From top to bottom, they are tempered glass, encapsulation film EVA, series batteries (connected in series or in parallel with welding strips and bus bars), encapsulation film EVA, and backplane. After stacking, they are placed in a laminator, and in a vacuum environment and at a temperature of 140°C, the airbag is squeezed from top to bottom from the backplane to the glass. EVA melts in an environment of 140°C, has fluidity and undergoes a cross-linking reaction, and has strong viscosity. After the laminator squeezes out the air between the layers, EVA makes the battery stick tightly between the tempered glass and the backplane, achieving a packaging effect. After lamination, each layer is encapsulated with a frame and sealed with a sealant. The junction box is fixed on the backplane, and the battery leads are connected to the external circuit through a connector.
[0006] EVA film has the advantages of low price, low processing temperature, good adhesion, and high light transmittance. However, photovoltaic modules will inevitably be in a high temperature and high humidity environment. Water vapor will penetrate the sealant, and EVA will undergo hydrolysis to produce acetic acid, which will cause corrosion of the battery components. The traditional method of solving the problem of water vapor in the components is to block the infiltration of water vapor with materials, such as using water-blocking glass, water-blocking film, water-blocking frame, water-blocking backplane, etc. However, the effect of these methods in blocking water vapor is still not good enough. Solar cells are still easily infiltrated with water under conditions of high temperature and high humidity, resulting in a significant decrease in their various performances, especially conversion efficiency. Summary of the invention
[0007] In view of the shortcomings and deficiencies of the prior art, the present invention provides an improved dehumidification material for solar cell packaging, which can effectively absorb water vapor that penetrates into the solar cell module, so that the solar cell can maintain stable performance such as conversion efficiency under high temperature and high humidity conditions.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A dehumidification material for solar cell packaging, the dehumidification material comprising glass fiber, and silicon dioxide and molecular sieves located on the glass fiber; the molecular sieve is a combination of one or more of 13X molecular sieve, 5A molecular sieve, 4A molecular sieve and 3A molecular sieve.
[0010] In the prior art, in order to solve the water vapor problem of solar cell modules, it is usually started from the material to block water vapor penetration, such as using water-blocking glass, water-blocking film, water-blocking frame, water-blocking backplane, etc. However, the effect of these methods in blocking water vapor is still not good enough, and solar cells are still easy to penetrate water under conditions such as high temperature and high humidity, resulting in a significant decrease in various performances, especially conversion efficiency. The inventor of the present application found through research that by arranging silicon dioxide and a specific type of molecular sieve (a combination of one or more of 13X molecular sieve, 5A molecular sieve, 4A molecular sieve, and 3A molecular sieve) on glass fiber, these types of molecular sieves are all dehumidifying molecular sieves, which can quickly absorb moisture and have excellent water-locking performance, and the dehumidifying material containing the specific type of molecular sieve is used for the encapsulation of solar cells, because the above-mentioned molecular sieve can absorb the water vapor that penetrates into the inside of the solar cell, prevent the influence of water vapor on the solar cell module, and then can greatly improve the encapsulation effect of the solar cell, so that it can withstand high temperature and high humidity environmental conditions, and the attenuation degree of the performance such as conversion efficiency under high temperature and high humidity conditions is obviously suppressed.
[0011] Dehumidification molecular sieve is a natural zeolite or artificially synthesized hydrated aluminum silicate (zeolite), which has the function of screening molecules. The most basic structure of the molecular sieve skeleton is SiO4 and AlO4 tetrahedron, which form a three-dimensional network structure through the combination of ordinary oxygen atoms. According to the different molecular ratios of SiO2 and Al2O3, molecular sieves of different pore sizes are obtained. Molecular sieves have the advantages of stable skeleton structure (skeleton collapse temperature is higher than 600℃), strong corrosion resistance, and strong adsorption capacity. The specific structure of the molecular sieve makes its combination with water molecules more stable, and the adsorption heat of water vapor is also relatively high. At higher temperatures, the adsorption capacity of some dehumidifiers (such as lithium chloride, silica gel, etc.) can be reduced to zero, but the molecular sieve can still maintain a relatively good effect. In addition, when the relative humidity is low, the dehumidification performance of adsorption materials such as silica gel decreases rapidly, but the molecular sieve can still maintain a high adsorption capacity. After the dehumidification molecular sieve adsorbs water, it can lock the water firmly, and still maintain a high adsorption capacity at temperatures above 100℃. At temperatures below 200℃, the water will not be desorbed.
[0012] In some embodiments, the ratio of the mass of the molecular sieve to the area of the glass fiber is 60-200 g: 1 m 2 .
[0013] In some embodiments, the mass of the silicon dioxide accounts for 4% to 40% of the mass of the molecular sieve.
[0014] In some embodiments, the glass fiber has a thickness of 75 to 120 μm.
[0015] In some embodiments, the glass fiber has a gram weight of 60-300 g / m 2 .
[0016] In some embodiments, the dehumidification material is prepared by a preparation method comprising the following steps: mixing raw materials including the molecular sieve, adhesive, additive and water to obtain slurry, immersing the glass fiber in the slurry, and calcining the glass fiber; the adhesive includes silica sol.
[0017] During the calcination process, organic matter and water will decompose or volatilize and no longer exist in the final dehumidification material. The adhesive in the slurry can make the molecular sieve bond smoothly to the glass fiber substrate, and the silica sol in the adhesive forms silicon dioxide after calcination. The additive can improve various properties of the slurry such as fluidity and dispersibility, which helps to evenly disperse the molecular sieve in the slurry and glass fiber.
[0018] In some embodiments, the slurry includes, by mass percentage, 20%-50% molecular sieve, 10%-30% adhesive, 0.08%-0.35% auxiliary agent and 19%-70% water.
[0019] Preferably, in terms of mass percentage, the slurry comprises 25%-40% molecular sieve, 10%-20% adhesive, 0.09%-0.3% auxiliary agent and 38%-65% water.
[0020] In some embodiments, the adhesive further comprises an aqueous dispersion of white latex or sepiolite.
[0021] In some embodiments, the auxiliary agent is selected from a combination of one or more of a wetting agent, a leveling agent, and a dispersant. The three auxiliary agents respectively improve the wetting, flow and dispersibility of the slurry.
[0022] In some embodiments, the solid content of the adhesive is 20%-40%.
[0023] In some embodiments, the auxiliary agent is a mixture of a wetting agent, a leveling agent, and a dispersant.
[0024] In some embodiments, the slurry includes, by mass percentage, 20%-50% molecular sieve, 10%-30% adhesive, 0.03%-0.1% wetting agent, 0.03%-0.1% leveling agent, 0.03%-0.1% dispersant and 19%-70% water.
[0025] The present invention also provides a method for preparing the above-mentioned dehumidification material for solar cell packaging, the preparation method comprising the following steps: mixing raw materials including the molecular sieve, adhesive, auxiliary agent and water to obtain slurry, impregnating the glass fiber in the slurry, and calcining the glass fiber to obtain the dehumidification material; the adhesive includes silica sol. The silica sol in the adhesive forms silicon dioxide after calcination, and during the calcination process, organic matter and water will decompose or volatilize and no longer exist in the final dehumidification material.
[0026] In some embodiments, the slurry includes, by mass percentage, 20%-50% molecular sieve, 10%-30% adhesive, 0.08%-0.35% auxiliary agent and 19%-70% water.
[0027] Preferably, in terms of mass percentage, the slurry comprises 25%-40% molecular sieve, 10%-20% adhesive, 0.09%-0.3% auxiliary agent and 38%-65% water.
[0028] In some embodiments, the adhesive further comprises an aqueous dispersion of white latex or sepiolite.
[0029] In some embodiments, the auxiliary agent is selected from a combination of one or more of a wetting agent, a leveling agent, and a dispersant.
[0030] In some embodiments, the solid content of the adhesive is 20%-40%.
[0031] In some embodiments, the auxiliary agent is a mixture of a wetting agent, a leveling agent, and a dispersant.
[0032] In some embodiments, the slurry includes, by mass percentage, 20%-50% molecular sieve, 10%-30% adhesive, 0.03%-0.1% wetting agent, 0.03%-0.1% leveling agent, 0.03%-0.1% dispersant and 19%-70% water.
[0033] In some embodiments, the dipping is performed 1 to 3 times.
[0034] In some embodiments, the immersion time is 10-30 minutes.
[0035] In some embodiments, the calcination temperature is 200-500°C.
[0036] The present invention also provides use of the dehumidification material for solar cell encapsulation in solar cell encapsulation.
[0037] The present invention also provides a solar cell assembly, comprising a panel, an upper encapsulation film, a solar cell layer, a lower encapsulation film, and a backplane, wherein the solar cell layer comprises solar cells and the aforementioned dehumidification material for solar cell encapsulation. By filling the dehumidification material in the cell gaps and the inside of the frame of the assembly device, the high temperature and high humidity resistance of the solar cell can be significantly improved.
[0038] In some embodiments, the solar cell sheets are multiple and are arranged at intervals, and the dehumidification material is located in the gaps between the multiple solar cell sheets.
[0039] In some embodiments, the thickness of the solar cell sheet is the same as the thickness of the dehumidification material.
[0040] In some embodiments, the width of the gap between two adjacent solar cells is 2-5 mm.
[0041] In some embodiments, multiple solar cells are connected in series.
[0042] In some embodiments, the plurality of solar cells have the same thickness and are located in the same horizontal plane.
[0043] In some embodiments, the plurality of solar cells are arranged in multiple rows and columns, each having the same size and shape, and a gap is provided between each two adjacent cells. The specific shape of the solar cell is not particularly limited, for example, it can be rectangular, square, circular, triangular, etc., preferably square.
[0044] In some embodiments, the front panel and the back panel are both tempered glass.
[0045] In some embodiments, the upper packaging film and the lower packaging film are both EVA.
[0046] In some embodiments, the solar cell module is selected from a TOPCon module, a PERC module or a HJT module.
[0047] In some embodiments, the preparation method includes the following steps: according to the pattern set by the target solar cell, the area of the dehumidification material corresponding to the pattern is cut out, and the solar cell is placed in the cut area of the dehumidification material to obtain the solar cell layer; the panel, the upper packaging film, the solar cell layer, the lower packaging film, and the backplane are stacked and laminated.
[0048] In some embodiments, the lamination is performed in a laminator.
[0049] In some embodiments, the lamination is performed in a vacuum environment at a temperature of 130-180°C.
[0050] In some embodiments, the laminate is pressed from above by a bladder.
[0051] Compared with the prior art, the present invention has the following advantages:
[0052] The dehumidification material for solar cell encapsulation of the present invention can effectively absorb water vapor that penetrates into the solar cell assembly, so that the solar cell can maintain stable performance such as conversion efficiency under high temperature and high humidity conditions.
[0053] The present invention arranges silicon dioxide and a specific type of molecular sieve on glass fiber to obtain a dehumidification material. By filling the dehumidification material in the gap between cells and the inside of the frame of a solar cell assembly device, the high temperature and high humidity resistance of the solar cell can be significantly improved, so that the conversion efficiency of the solar cell can be kept stable under high temperature and high humidity conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 is a schematic structural diagram of a solar cell assembly of the present invention;
[0055] Figure 2 A top view of a solar cell assembly of the present invention;
[0056] Among them, 1- panel, 2- upper packaging film, 3- solar cell layer, 4- lower packaging film, 5- back plate, 6- solar cell sheet, 7- dehumidification material. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0058] Example 1
[0059] This embodiment provides a dehumidification material and a packaged solar cell:
[0060] Preparation of dehumidification material: Add 0.9kg silica sol (its solid content is 30%, which accounts for about 15.2wt% of the total slurry, purchased from Shandong Better New Materials Co., Ltd.) to 3kg deionized water, then add 3g wetting agent, 3g dispersant, 3g leveling agent (the three account for about 0.051wt% of the total slurry), mix well, then add 2kg 5A dehumidification molecular sieve (which accounts for about 33.8wt% of the total slurry, purchased from Luoyang Jianlong Micro-Nano New Materials Co., Ltd.), use a disperser to disperse, and prepare a uniform slurry. Select 100μm thick, gram weight 120g / m 2Glass fiber paper. The glass fiber paper is immersed in the slurry and taken out after 10 minutes. The molecular sieve coating amount is about 70g / m 2 . Then roast at 300℃ to remove excess organic matter and moisture.
[0061] Preparation of solar cell modules:
[0062] like Figure 1 As shown, the solar cell assembly includes, from top to bottom, a panel 1, an upper encapsulation film 2, a solar cell layer 3, a lower encapsulation film 4 and a back sheet 5, wherein the solar cell layer 3 includes solar cells 6 and the aforementioned prepared dehumidification material 7. The solar cells 6 are multiple and arranged at intervals, and the dehumidification material 7 is located in the gaps between the multiple solar cells 6. The thickness of the two is the same, and there is no dehumidification material 7 on the upper side or the lower side of the solar cell 6.
[0063] like Figure 2 As shown, in the solar cell layer 3, a plurality of solar cells 6 are arranged in multiple rows and columns at intervals, and the shape of the solar cells 6 is square (but the present invention does not limit the specific shape of the solar cell 6), each cell has the same size and shape, and a gap is set between each adjacent cell. Figure 2 The wider gap is 1.5 mm, and the narrower gap is 1 mm. The dehumidification material 7 is located in all the gaps. The multiple solar cells 6 are arranged in series (but the present invention does not limit the circuit connection method of the multiple solar cells 6).
[0064] According to the size and pattern of the components, cut off the aforementioned dehumidification material in the cell area, put the PERC cell into the cut dehumidification material, and the welded cell will be stacked with the packaging material. From top to bottom, they are tempered glass, EVA film, solar cell layer 3 composed of series cells / dehumidification materials, EVA film, and tempered glass. After stacking, put it in a laminator and squeeze it from top to bottom by an airbag in a vacuum environment and at a temperature of 140°C. The EVA film melts at 140°C, has fluidity and undergoes a cross-linking reaction, and has strong viscosity. After the laminator squeezes out the air between the layers, the EVA film makes the battery stick tightly to the middle of the tempered glass, achieving a packaging effect.
[0065] Example 2
[0066] This embodiment provides a dehumidification material and a packaged solar cell:
[0067] Preparation of dehumidification material: Add 1.1kg silica sol (its solid content is 30%, which accounts for about 19.6wt% of the total slurry, purchased from Shandong Better New Materials Co., Ltd.) to 2.5kg deionized water, then add 3g wetting agent, 3g dispersant, 3g leveling agent (the three account for about 0.053wt% of the total slurry), mix well, then add 2kg 13X dehumidification molecular sieve (which accounts for about 35.7wt% of the total slurry, purchased from Luoyang Jianlong Micro-Nano New Materials Co., Ltd.), use a disperser to disperse, and prepare a uniform slurry. Select 90μm thick, gram weight 130g / m 2 Glass fiber paper. The glass fiber paper is impregnated with the slurry and taken out after 20 minutes. The molecular sieve coating amount is about 150g / m 2 . Then roast it at 400℃ to remove excess organic matter and moisture.
[0068] Preparation of solar cell modules:
[0069] like Figure 1 As shown, the solar cell assembly includes, from top to bottom, a panel 1, an upper encapsulation film 2, a solar cell layer 3, a lower encapsulation film 4 and a back sheet 5, wherein the solar cell layer 3 includes solar cells 6 and the aforementioned prepared dehumidification material 7. The solar cells 6 are multiple and arranged at intervals, and the dehumidification material 7 is located in the gaps between the multiple solar cells 6. The thickness of the two is the same, and there is no dehumidification material 7 on the upper side or the lower side of the solar cell 6.
[0070] like Figure 2 As shown, in the solar cell layer 3, a plurality of solar cells 6 are arranged in multiple rows and columns at intervals, and the shape of the solar cells 6 is square (but the present invention does not limit the specific shape of the solar cell 6), each cell has the same size and shape, and a gap is set between each adjacent cell. Figure 2 The wider gap is 1.5 mm, and the narrower gap is 1 mm. The dehumidification material 7 is located in all the gaps. The multiple solar cells 6 are arranged in series (but the present invention does not limit the circuit connection method of the multiple solar cells 6).
[0071] According to the size and pattern of the components, cut off the aforementioned dehumidification material in the cell area, put the TOPCon cells into the cut dehumidification material, and the welded cells will be stacked together with the packaging material. From top to bottom, they are tempered glass, EVA film, solar cell layer 3 consisting of series cells / dehumidification materials, EVA film, and tempered glass. After stacking, put it in a laminator and squeeze it from top to bottom by an airbag in a vacuum environment and at a temperature of 140°C. The EVA film melts at 140°C, has fluidity and undergoes a cross-linking reaction, and has strong viscosity. After the laminator squeezes out the air between the layers, the EVA film makes the battery stick tightly to the middle of the tempered glass, achieving a packaging effect.
[0072] Comparative Example 1
[0073] This comparative example provides a dehumidification material and a packaged solar cell. The dehumidification material and the packaged solar cell are basically the same as those in Example 1, except that when preparing the dehumidification material, 5A molecular sieve is not added to the slurry.
[0074] Comparative Example 2
[0075] This comparative example provides a dehumidification material and a packaged solar cell: they are basically the same as Example 1, except that: when preparing the dehumidification material, Y molecular sieve is used to replace 5A molecular sieve.
[0076] According to the IEC61215 and IEC61730 reliability test standards, the encapsulated solar cell modules in each embodiment and comparative example were subjected to a damp heat (DH) test, i.e., a damp heat test test, by placing the modules in an environmental test box at a high temperature of 85°C and a high humidity of RH85% for 1000, 2000, and 3000 hours. The attenuation percentage of the conversion efficiency of the solar cell module after the residence (relative percentage of the conversion efficiency before the residence) was calculated, and the results are shown in Table 1 below.
[0077] Table 1 Performance of each embodiment and comparative example
[0078] DH1000 Attenuation DH2000 Attenuation DH3000 Attenuation Example 1 2.93% 3.84% 5.63% Example 2 1.42% 2.86% 3.45% Comparative Example 1 3.24% 4.41% 9.37% Comparative Example 2 3.21% 4.32% 9.29%
[0079] It can be seen that the attenuation degree of conversion efficiency of the solar cell module of the embodiment of the present invention under high temperature and high humidity conditions is significantly lower than that of the comparative example. It can be seen that the present invention can significantly improve the moisture absorption performance of the dehumidification material by arranging a specific type of molecular sieve on the glass fiber, and when it is used for the packaging of solar cell modules, the module's ability to withstand high temperature and high humidity can be significantly improved.
[0080] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0081] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A dehumidification material for solar cell encapsulation, characterized in that: The dehumidification material includes glass fiber, and silicon dioxide and molecular sieve located on the glass fiber; the molecular sieve is a combination of one or more of 13X molecular sieve, 5A molecular sieve, 4A molecular sieve and 3A molecular sieve.
2. The dehumidification material for solar cell encapsulation according to claim 1, characterized in that: The ratio of the mass of the molecular sieve to the area of the glass fiber is 60-200 g: 1 m 2 ; and / or, the mass of the silicon dioxide accounts for 4%-40% of the mass of the molecular sieve; and / or, the thickness of the glass fiber is 75-120 μm, and / or, the gram weight of the glass fiber is 60-300 g / m 2 .
3. The dehumidification material for solar cell encapsulation according to claim 1, characterized in that: The dehumidification material is prepared by a preparation method comprising the following steps: mixing raw materials including the molecular sieve, adhesive, additive and water to obtain slurry, dipping the glass fiber in the slurry, and calcining the glass fiber; the adhesive comprises silica sol.
4. The dehumidification material for solar cell encapsulation according to claim 3, characterized in that: In terms of mass percentage, the slurry comprises 20%-50% molecular sieve, 10%-30% adhesive, 0.08%-0.35% additive and 19%-70% water; preferably, in terms of mass percentage, the slurry comprises 25%-40% molecular sieve, 10%-20% adhesive, 0.09%-0.3% additive and 38%-65% water; and / or, the adhesive further comprises an aqueous dispersion of white latex or sepiolite; and / or, the additive is selected from a combination of one or more of a wetting agent, a leveling agent and a dispersant.
5. The dehumidification material for solar cell encapsulation according to claim 4, characterized in that: The solid content of the adhesive is 20%-40%; and / or, the auxiliary agent is a mixture of a wetting agent, a leveling agent, and a dispersant; and / or, in terms of mass percentage, the slurry includes 20%-50% molecular sieve, 10%-30% adhesive, 0.03%-0.1% wetting agent, 0.03%-0.1% leveling agent, 0.03%-0.1% dispersant and 19%-70% water.
6. A method for preparing a dehumidification material for solar cell encapsulation according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: mixing raw materials including the molecular sieve, adhesive, auxiliary agent and water to obtain slurry, dipping the glass fiber into the slurry, and calcining the glass fiber to obtain the dehumidification material; the adhesive comprises silica sol.
7. A solar cell assembly, comprising a panel, an upper packaging film, a solar cell layer, a lower packaging film, and a back sheet, characterized in that: The solar cell layer comprises a solar cell sheet and the dehumidification material for solar cell encapsulation according to any one of claims 1 to 5.
8. The solar cell assembly according to claim 7, characterized in that: The solar cell sheets are multiple and arranged at intervals, and the dehumidification material is located in the gaps between the multiple solar cell sheets; and / or the thickness of the solar cell sheets is the same as the thickness of the dehumidification material; and / or the panel and the back panel are both tempered glass; and / or the upper packaging film and the lower packaging film are both EVA; and / or the solar cell module is selected from a TOPCon module, a PERC module or a HJT module.
9. The solar cell assembly according to claim 8, characterized in that: The width of the gap between two adjacent solar cells is 2-5 mm; and / or, the multiple solar cells are arranged in series; and / or, the multiple solar cells have the same thickness and are located in the same horizontal plane; and / or, the multiple solar cells are arranged in multiple rows and columns, each of which has the same size and shape, and a gap is set between each two adjacent cells.
10. A method for preparing a solar cell module according to any one of claims 7 to 9, characterized in that: The preparation method comprises the following steps: according to the pattern set by the target solar cell, cutting out the area of the dehumidification material corresponding to the pattern, placing the solar cell in the cut area of the dehumidification material to obtain the solar cell layer; and stacking and laminating the panel, the upper packaging film, the solar cell layer, the lower packaging film and the backplane.
Citation Information
Patent Citations
Method for in situ tailoring the metallic component of ceramic articles and articles made thereby
IE61215B1
Cited By
Quinoxaline organic polymer as well as preparation method and application thereof
CN121021812A
A quinoxaline-based organic polymer, its preparation method and application
CN121021812B